2005
DOI: 10.1002/jcb.20661
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β induces osteopontin expression in pulmonary fibroblasts

Abstract: Osteopontin is a multifunctional matricellular protein identified as one of the most upregulated genes in pulmonary fibrosis. Experimental animal models have identified early pro-fibrotic cytokines as essential to the pathogenesis of inflammation-induced pulmonary fibrosis. However, the principal sources of osteopontin in the fibroproliferative lung, and the factors responsible for its induction, have not been fully defined. We isolated primary rat lung fibroblasts in culture to examine the expression and regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 37 publications
3
23
0
Order By: Relevance
“…In accordance with our finding, a previous study showed that no OPN expression was found in tissue sections of a limited number of non-asthmatic control subjects 6. Previous in vitro studies have shown that OPN is produced by fibroblasts as well as by several murine immune cell types such as macrophages, T cells, B cells and mast cells 13 26 27. We were unable to identify the cells responsible for OPN production in the current study since the inflammatory cells assessed by induced sputum reflect the cellular content of the lower airway lining fluid and not the subepithelial layers that seem to represent the basic cellular source of OPN 6 15…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our finding, a previous study showed that no OPN expression was found in tissue sections of a limited number of non-asthmatic control subjects 6. Previous in vitro studies have shown that OPN is produced by fibroblasts as well as by several murine immune cell types such as macrophages, T cells, B cells and mast cells 13 26 27. We were unable to identify the cells responsible for OPN production in the current study since the inflammatory cells assessed by induced sputum reflect the cellular content of the lower airway lining fluid and not the subepithelial layers that seem to represent the basic cellular source of OPN 6 15…”
Section: Discussionsupporting
confidence: 92%
“…26) Consequently, it promotes inflammation, leukocyte infiltration, granuloma formation, and tissue fibrosis. 27) Our results indicate that DBD glycoprotein inhibited the expression of IL-1 and COX-2 and the production of nitric oxide in PMACI-stimulated HMC-1 cells, suggesting its antiinflammatory properties. Recently, it has been found that both COX-2 and inducible NOS (iNOS) play important roles in various inflammatory diseases.…”
Section: Discussionsupporting
confidence: 51%
“…25,26 Consequently, they promote inflammation, Figure 2. Inhibitory effect of CTB glycoprotein on the phosphorylation of ERK1/2 and p38 MAPK in DHEP (100 mM) stimulated HMC-1 Cells.…”
Section: Discussionmentioning
confidence: 99%
“…C, control leukocyte infiltration granuloma formation, and tissue fibrosis. 26 In addition, COX-2 is an inducible enzyme found at low concentrations in healthy tissues, but its expression becomes elevated in response to tissue damage during inflammation. Several studies have reported that PGD2, which is the major COX-2 metabolite released from activated mast cells, stimulates the pathogenesis of eosinophilic airway inflammation.…”
Section: Discussionmentioning
confidence: 99%